Will I Regret It? Anticipated Negative Emotions Modulate Choices in Moral Dilemmas - Pletti, Carolina; Lotto, Lorella; Tasso, Alessandra; Sarlo, Michela (Frontiers in Psychology, 2016)
We tested if post-decisional emotions of regret, guilt, shame, anger, and disgust can account for individuals’ choices in moral dilemmas depicting the choice of letting some people die (non-utilitarian option) or sacrificing one person to save them (utilitarian option). We collected participants’ choices and post-decisional emotional ratings for each option using Footbridge-type dilemmas, in which the sacrifice of one person is the means to save more people, and Trolley-type dilemmas, in which the sacrifice is only a side effect. Moreover, we computed the EEG Readiness Potential to test if the neural activity related to the last phase of decision-making was related to the emotional conflict. Participants reported generally stronger emotions for the utilitarian as compared to the non-utilitarian options, with the exception of anger and regret, which in Trolley-type dilemmas were stronger for the non-utilitarian option. Moreover, participants tended to choose the option that minimized the intensity of negative emotions, irrespective of dilemma type. No significant relationship between emotions and the amplitude of the Readiness Potential emerged. It is possible that anticipated post-decisional emotions play a role in earlier stages of decision-making.